Evaluation of the Results of Arthroscopic Anterior Cruciate Ligament Reconstruction with Peroneus Longus Autograft - Hasan, Md Abul; Morshed, Taufiq; Alam, Md Khorshedul; Matin, Md Asraf ul; Roy, Liton Kumar; Rahman, Md Minhazur; Hasan, Md Israt; Ahmed, Md Bulbul (Journal of Comilla Medical College Teachers’ Association, 2025)
Background: Restoring functional knee stability often involves reconstructing the anterior cruciate ligament (ACL). Due to its robustness, consistent clinical results, and minimal donor-site injury, the peroneus longus tendon is a good graft option. Methods: Our study was a retrospective study that samples ACL repair patients sequentially from February 2023 to June 2024. Based on history, clinical examination and MRI findings, an ACL rupture was diagnosed. Twenty patients were undergoing ACL reconstruction using peroneus longus tendon autograft after fulfilling inclusion criteria and obtaining informed consent. They were assessed preoperatively postoperatively and follow up for 1 year. Results: Mean age of the patients was 27.4±7.26 years. At final follow up, 2 patients had positive Lachman and anterior drawer test. The average length of the peroneus longus tendon was 28.7±1.11 cm and the average diameter was 8.4±0.28 mm. Average hospital stay was 3.7±0.79 days. The IKDC, modified Cincinnati and Tegner-Lysholm score were improved significantly after 12 months of operation. The mean AOFAS scores and mean FADI score were 95.50±6.16 and 114.90±24.50 respectively after 12 months. There was one postoperative infection which was healed after antibiotic prescription. One patient had postoperative stiffness which was persisted after 1 year. Conclusion: Arthroscopic ACL reconstruction with PLT appears to be a promising alternative to traditional graft options, such as hamstring or patellar tendons. J Com Med Col Teachers’ Asso Jan 2025; 29(1): 26-31